1978
DOI: 10.1212/wnl.28.6.567
|View full text |Cite
|
Sign up to set email alerts
|

Meningiomas in five members of a family over two generations, in one member simultaneously with acoustic neurinomas

Abstract: Despite four reports of familial occurrence of meningiomas, the inheritance of this tumor remains an open question. We describe a family in which four members in two generations had meningiomas without evidence of neurofibromatosis. Another member of the family, however, had multiple meningiomas and bilateral acoustic neurinomas, while yet another had multiple café-au-lait spots. We suspect that a highly unusual presentation of neurofibromatosis explains this otherwise very unlikely occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The patients mentioned here are members of a family that was described by Delleman et al (18) as having the central form of Von Recklinghausen disease. Figure 2A depicts the updated pedigree.…”
Section: Patientsmentioning
confidence: 99%
“…The patients mentioned here are members of a family that was described by Delleman et al (18) as having the central form of Von Recklinghausen disease. Figure 2A depicts the updated pedigree.…”
Section: Patientsmentioning
confidence: 99%
“…12 Cases of multiple familial meningiomas without evidence of neurofibromatosis occur. [29][30][31] Multiple spinal canal meningiomas are very rare; about 10 cases from the United States have been reported. 32 A case of multiple meningiomas in a child was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Familial occurrence of brain tumours, in particular, has been demonstrated in numerous families l, 3,4,10,13 The occurrence of brain tumour in association with malignancies at other sites in the same patient has been frequently reported 2'7' 12,15 and there are several reports of brain tumours and extraneural malignancies among members of the same family 12. Genetic studies of brain tumour patients, however, seem to be rare and have showed contradictory results s' 6, 9…”
Section: Introductionmentioning
confidence: 99%